Hotels impact on the environment - Dovgun, Irina; Chala, Kateryna (My University, 2014)
Despite tourism being a profitable economic sector, its benefits are frequently accompanied by many negative environmental impacts. Some hotels around the world have implemented important greening initiatives to reduce their impact on the environment. They include energy, water, waste, etc.
Keywords: hotel; environment; готель; навколишнє середовище; кафедра іноземних мов професійного спрямування